Law Enforcement of Jinayat Cases in Syar’iyah Court in Aceh Province Indonesia During Covid-19 Pandemic - Usman, Mizaj Iskandar; Yahya, Azhari; Jafar, M.; Darmawan, Darmawan; Kurdi, Muliadi (UUM Press, 2023)
This study aims to look at the jinayat (criminal) trial both from the regulatory aspect and the application of the rule as a response to the outbreak of the COVID-19 pandemic. Therefore, this study uses two approaches at once, a normative approach to examine the legality of the regulations and a sociological approach to examine the application of the rule in Syar’iyah courts throughout Aceh. This study found that the Supreme Court has issued the Supreme Court Regulation known as Perma Number 4 of 2020 as the basic regulation for the implementation of virtual criminal and jinayat trials. There is a diversity of practices that lead to legal uncertainty in the application of Perma at the Aceh Syar’iyah court. There are several Syar’iyah courts that have implemented Perma. However, there are also many Syar’iyah courts that ignore Perma due to unprepared infrastructure. But, there are also some Syar’iyah courts that conduct jinayat trials based on the agreement of the parties involved in the trial. In this case, jinayat trials are sometimes carried out virtually and sometimes physically present in the courtroom. This study also found that the tendency of jinayat cases increased throughout the year 2020 when the pandemic occurred. The increase in jinayat cases was caused by two reasons. First, almost all criminal acts regulated in the qanun of jinayat are domestic crimes. Second, there was a relatively large deduction amount of the budget for the enforcement of Islamic law, which was then reallocated to prevent the spread of COVID-19.